Isolation and purification of antibacterial lipopeptides from Bacillus velezensis YA215 isolated from sea mangroves - Yu, FuTian; Shen, YuanYuan; Qin, YaLi; Pang, YiYang; Fan, HeLiang; Peng, JingJing; Pei, XiaoDong; Liu, XiaoLing (Frontiers in Nutrition, 2022)
The increasing burden and health risks of antimicrobial resistance (AMR) pose a great threat to society overall. Lipopeptides exhibit great potential as novel and safe alternatives to traditional antibiotics. In this study, the strain YA215, which was isolated from the mangrove area in Beibu Gulf, Guangxi, China, was identified as Bacillus velezensis based on morphological and 16S rRNA gene sequences. Then, the antimicrobial activity of YA215 lipopeptide extracts (YA215LE) from B. velezensis, which was obtained by combining hydrochloric acid precipitation and methanol extraction, was evaluated by an agar well diffusion method, and the results showed that YA215LE exhibited inhibitory activity on the indicator strains of gram-positive bacteria, gram-negative bacteria, and fungi. Additionally, based on LC‒MS/MS analysis, YA215LE contained three groups of lipopeptides (surfactin, iturin and fengycin). Furthermore, one separation fraction (BVYA1) with significant antibacterial activity was obtained by gel column chromatography and semipreparative reverse-phase high-performance liquid chromatography (RP-HPLC) separation. Additionally, LC‒MS analysis of BVYA1 showed three molecular ion peaks corresponding to conventional surfactin homologs (MH +: m/z 980.62; 994.66; 1008). By MS/MS analysis, BVYA1 was identified as sufactin with the precise amino acid sequence Glu - Leu/Ile - Leu - Val - Asp - Leu - Leu/Ile and hydroxyl fatty acids with 11 to 13 carbons. [M + H]+ at m/z 980.62 corresponded with a heptapeptide sequence Glu - Leu/Ile - Leu - Val - Asp - Leu - Leu/Ile, and the C11 β-hydroxy fatty acid chain was detected for the first time in B. velezensis, which demonstrates that the strain corresponds to a new surfactin variant. In particular, BVYA1 showed antibacterial activity with the minimum inhibitory concentration (MIC) values of 7.5 µg/mL, 15 µg/mL and 15 µg/mL against Escherichia coli, Salmonella and Shigella, respectively. Finally, the preliminary mechanism of inhibiting E. coli treated with BVYA1 was derived by scanning electron microscopy (SEM) and calcein-AM/PI double-staining assays. The results showed that BVYA1 effectively permeabilized the cytoplasmic membrane and disrupted the morphology of targeted bacterial cells. In conclusion, this study suggests that the YA215LE from B. velezensis YA215 might be a potential candidate for a bactericide.